Beyond Data Recovery: Developing Digital Information Systems for Cultural Resources in the Online Era. Issue 3 (August 2020) - Wollwage, Lance K.; Brooks, Allyson; Smith, Rob; McLemore, Morgan; Strader, Annie; Gant, Kim
ABSTRACT: For historic property types such as archaeological sites and historic buildings, data recovery is often the main part of mitigation plans offered by federal agencies with undertakings that will destroy part or all of a cultural resource. In theory, by extracting important information before destruction, we recover some part of a historic resource's cultural value. In some situations, however, data recovery is impossible or otherwise undesirable, and "creative" or off-site mitigation measures are necessary to mitigate adverse effects. In such circumstances, the Washington State Department of Archaeology and Historic Preservation has accepted funding from federal agencies to create, implement, and enhance an online digital information system for cultural resources. This article describes the Washington Information System for Architectural and Archaeological Records Data (WISAARD) and provides an example of a federal agency funding WISAARD development as creative mitigation for the transfer of archaeological sites out of federal ownership. We discuss the benefits of such systems and address how their development meets preservation goals established by the Advisory Council on Historic Preservation.